Pregnancy Diagnosis with Progesterone ELISA Kit in Farm Animals, Its Accuracy and Application - Nepal, Sambriddhi; Subedi, Deepak; Kaphle, Krishna (Nepalese Veterinary Journal, 2019)
Pregnancy is a special condition where a female lodges one or more young ones within her uterus. It is maintained by various endocrine physiology and metabolic changes between maternal and fetal circumstances. Space dine secreted by corpus luteum increases extraordinarily throughout the pregnancy, estrogen increases rapidly during first trimester and prolonged lifespan of corpus luteum and small quantity of estrogen prevents prostaglandins pulsatic secretion. We reviewed available literature to evaluate the accuracy of progesterone ELISA test kit in pregnancy diagnosis in farm animals. We found varying accuracy in global and Nepalese context but found that this is an important tool for early pregnancy diagnosis and infertility monitoringwith high accuracy which contributes to increase economic efficiency of a farm. This kit has been used for qualitative and quantitative study of progesterone to understand the reproductive status of animals. Therefore, its use is increasing in globally and in Nepal. This kit has been used at various breeding centers, and livestock service centers of Nepal. However, wider level use is still difficult due to lack of infrastructuresand subsistence farming.